Can Gender-Fair Language Reduce Gender Stereotyping and Discrimination? - Sczesny, Sabine; Formanowicz, Magda; Moser, Franziska (Frontiers in Psychology, 2016)
Gender-fair language (GFL) aims at reducing gender stereotyping and discrimination. Two principle strategies have been introduced to make languages gender-fair and to treat women and men symmetrically: neutralization and feminization. Neutralization is achieved, for example, by replacing male-masculine forms (policeman) with gender-unmarked forms (police officer), whereas feminization relies on the use of feminine forms to make female referents visible (i.e., the applicant ... he or she instead of the applicant ... he). Integrating research on language structures, language policies, and individual language behavior, the present paper provides an overview of whether and under what circumstances GFL contributes to the reduction of gender stereotyping and discrimination.